Impactos ambientais e (in)sustentabilidade no perímetro irrigado da Macela, Itabaiana - Gomes, Viviane Ramos (2004)
The goal of this work was to evaluate environmental impacts and (un)sustainability of the irrigated perimeter of Macela, located in Itabaiana city - Sergipe - Brazil, important area of vegetable crops. The local problematic is focused on untreated sewage and tannery wastes in the dam, plus the intensive and indiscriminate use of pesticides. Aiming to evaluate the dimension of this problematic, water samples has been collected along the dam. The following parameters were evaluated: total and termotolerants coliforms, pH, DO (Dissolved Oxygen), BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), turbidity, TDS (Total Dissolved Solids), salinity, chlorides, color, total hardness, alkalinity, nitrate, nitrite, ammonia, phosphate and chromium VI. The existence of pesticides residues in water and foods obtained from the dam was also approached. The analytical procedures are in accordance with Clesceri et al. (1998). Results have shown that the water is improper for bathing and are deprived of characteristics as being of class 2, mainly concerning total and temotolerants coliforms, pH, BOD, TDS, chlorides, color, ammonia and phosphate. Moreover, it is inadequate for irrigation, especially because of its large amount of coliforms and salinity. The behavior of agricultural workers towards the use of pesticides was evaluated and data have shown that all workers use pesticides in a constant way, without criteria of dosage and application specificity. However, about 16% of the analyzed samples have been rejected by large amount of methamidophos and carbofuran residues. The data reveals that workers seem ill-informed and unaware of the pesticides risks to health and the environment. In this direction, it is urgent an action from the competent authorities in order to control the negative impacts on the dam, to spread the technical knowledge. Such action will enable the stakeholders to take more conscientious decisions. A constant check in food quality is also necessary. These measures will surely contribute to sustainable development.